Finland : 2001 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Finland. (IMF Staff Country Reports; Country Report ;, 2001)
Finland's performance has been impressive. In light of rapid population aging, a significant and durable increase in the employment rate is vital. To leave room for needed tax cuts on labor while maintaining sufficiently large fiscal surpluses is crucial. With both growth and inflation set to slow, the current cyclical outlook offers an excellent opportunity for a taxed-based fiscal easing. Pension reform will ease the consequences of the demographic shock substantially. The private services sector in Finland has very strong potential for employment creation and growth.